Offrandes - Varèse, Edgard 1883-1965; Eda-Pierre, Christiane 1932-2020; Amy, Gilbert 1936-; Le Domaine musical (Paris, France) (Paris Disques Adès, 1969)
'Impact de la musique contemporaine' was a series of lavishly designed 7" records under Gilbert Amy's direction of Le Domaine musical, a society founded by Pierre Boulez, Hermann Scherchen, and Jean-Louis Barrault.
Perforated record cover. Portrait of Varèse on the record label.
Keywords: 20th Century (1901-2000); Vocal music; Avant-garde